(untitled) (PUBMET, 2022)
Citizen Science is one of the tiles in the open science mosaic, as it involves general public in science and keeps it informed about research results and methods. Its growing importance is reflected in scientific research policies across the European Research Area and is an integral part of the Responsible Research and Innovation (RRI) policy. The European Commission has been promoting this concept for many years and has strongly supported it financially through Horizon 2020 with more than 460 million euros for Science with and for Society (SwafS) sub-programme. Citizen Science projects in Slovenia have been running in different ways for a long time but still await systematic funding through national research co-funding instruments. One way to do it is to set up a national contact point for citizen science (NCPCS) announced in Slovenia‘s Research and Innovation Strategy 2021–2030. Here we present our analysis on which we will try to build the NCPCS. We will present the current state of Citizen Science in Slovenia with its organisational challenges, some Citizen Science projects, and a vision of NCPCS structure and function. We will also discuss the role of university libraries in creating and managing NCPCS. So far, information about existing projects had to be collected manually by monitoring institutional webpages or through personal contacts, which is less than optimal. A relatively large number of projects are currently underway, but they are poorly linked or visible. NCPCS should be set up on recommendations such as BESPOC (Broad Engagement in Science, Point of Contact) and good international practices such as those of Österreich forscht (Austria, https://www.citizen-science.at/en/), Bürger schaffen Wissen (https://www.buergerschaffenwissen.de/) or Citizen Science Network Switzerland (Switzerland, https://citizenscience.ch/de/). The key tasks of the NCPCS should be: ▸ Active monitoring, promoting, and documenting Citizen Science projects, ▸ Reviewing and promoting infrastructures that will be available to researchers for the implementation of Citizen Science projects, ▸ Connecting different stakeholders, ▸ Promoting the production of various documents in the Slovenian language for the implementation of Citizen Science projects, such as the Citizen Science Toolkit, ▸ Support in crowdsourcing for projects, ▸ International cooperation. We will pay special attention to supporting the development of the Citizen Science concept at universities and to including a network of Slovenian public libraries to support Citizen Science projects at the local level.